2011
DOI: 10.1126/scitranslmed.3002302
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Safety of Adjuvanted Vaccines

Abstract: Despite the very low risk-to-benefit ratio of vaccines, fear of negative side effects has discouraged many people from getting vaccinated, resulting in reemergence of previously controlled diseases such as measles, pertussis, and diphtheria. Part of this fear stems from the lack of public awareness of the many preclinical and clinical safety evaluations that vaccines must undergo before they are available to the general public, as well as from misperceptions of what adjuvants are or why they are used in vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 76 publications
0
41
0
Order By: Relevance
“…Despite their clear benefits and widespread use in vaccines, until recently, the only adjuvant licensed worldwide for clinical use was alum. 10 More recently, MF-59, an oil-in-water solution based on squalene, has been licensed as a vaccine adjuvant for influenza vaccines. 11 Furthermore, a derivative of lipopolysaccharide (LPS), the monophosphoryl lipid-A (MPL), has been approved recently for use as one of the components of the AS04 adjuvant (alum ϩ MPL) used in Cervarix, 12,13 the vaccine against cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their clear benefits and widespread use in vaccines, until recently, the only adjuvant licensed worldwide for clinical use was alum. 10 More recently, MF-59, an oil-in-water solution based on squalene, has been licensed as a vaccine adjuvant for influenza vaccines. 11 Furthermore, a derivative of lipopolysaccharide (LPS), the monophosphoryl lipid-A (MPL), has been approved recently for use as one of the components of the AS04 adjuvant (alum ϩ MPL) used in Cervarix, 12,13 the vaccine against cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 TLR ligands (TLR-Ls) represent an emerging new class of molecules with great potential as vaccine adjuvants. [3][4][5]8,10 Several TLR-dependent compounds are in advanced preclinical and clinical trials (eg, cytosine-phosphate-guanine oligodeoxynucleotide [CpG-ODN], 10 poly I-C/L-C, 10 and glucopyranosyl lipid adjuvant 14 ) and some have already been licensed for clinical use as adjuvants (eg, MPL-AS04 13 ) or therapeutics (eg, imidazoquilines 15 ). TLRs sense a wide range of pathogen-associated molecular patterns from bacteria, viruses, and parasites (reviewed in Kawai and Akira 16 and in Takeuchi and Akira 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…The combined adjuvant was highly effective in all cases. While various adjuvants under development exhibit efficacy in preclinical models, U.S. regulators have considerable safety concerns regarding adjuvants and vaccine reactogenicity that must be addressed (12,13,(25)(26)(27). 1Z105 and 1V270 demonstrate little in vitro toxicity (14,19).…”
mentioning
confidence: 99%
“…35,36 AS03 is a combination of a-tocopherol (vitamin E) and squalene in an oil-inwater emulsion and was extensively used in European global immunization campaigns during the 2009 pandemic with an estimated 380,000 pregnant women receiving this vaccine. [37][38][39][40] While one retrospective study in pregnant women suggested a trend to increased gestational diabetes and eclampsia in those that received MF59-adjuvanted influenza vaccine, 41 other studies have not reported similar effects during pregnancy. [42][43][44][45] A randomized controlled clinical trial comparing MF59-adjuvanted vaccine (Focetria Ò ) in pregnant and non-pregnant women found that a non-significant trend to a lower antibody response in pregnant women; 72% of the women reported adverse reactions, with 64% experiencing local reactions and 26% systemic reactions with malaise as the most common symptom.…”
Section: Adjuvanted Influenza Vaccines In Pregnancymentioning
confidence: 98%